Assessment of the consistency of health and demographic surveillance and household survey data: A demonstration at two HDSS sites in The Gambia. - Momodou Jasseh; Anne J Rerimoi; Georges Reniers; Ian M Timæus (PLoS ONE, 2022)
Objective To assess whether an adapted Demographic and Health Survey (DHS) like cross-sectional household survey with full pregnancy histories can demonstrate the validity of health and demographic surveillance (HDSS) data by producing similar population structural characteristics and childhood mortality indicators at two HDSS sites in The Gambia-Farafenni and Basse. Methods A DHS-type survey was conducted of 2,580 households in the Farafenni HDSS, and 2,907 in the Basse HDSS. Household members were listed and pregnancy histories obtained for all women aged 15-49. HDSS datasets were extracted for the same households including residency episodes for all current and former members and compared with the survey data. Neonatal (0-28 days), infant (<1 year), child (1-4 years) and under-5 (< 5 years) mortality rates were derived from each source by site and five-year periods from 2001-2015 and by calendar year between 2011 and 2015 using Kaplan-Meier failure probabilities. Survey-HDSS rate ratios were determined using the Mantel-Haenszel method. Results The selected households in Farafenni comprised a total population of 27,646 in the HDSS, compared to 26,109 captured in the household survey, implying higher coverage of 94.4% (95% CI: 94.1-94.7; p<0.0001) against a hypothesised proportion of 90% in the HDSS. All population subgroups were equally covered by the HDSS except for the Wollof ethnic group. In Basse, the total HDSS population was 49,287, compared to 43,538 enumerated in the survey, representing an undercount of the HDSS by the survey with a coverage of 88.3% (95% CI: 88.0-88.6; p = 1). All sub-population groups were also under-represented by the survey. Except for the neonatal mortality rate for Farafenni, the childhood mortality indicators derived from pregnancy histories and HDSS data compare reasonably well by 5-year periods from 2001-2015. Annual estimates from the two data sources for the most recent quinquennium, 2011-2015, were similar in both sites, except for an excessively high neonatal mortality rate for Farafenni in 2015. Conclusion Overall, the adapted DHS-type survey has reasonably represented the Farafenni HDSS database using population size and structure; and both databases using childhood mortality indicators. If the hypothetical proportion is lowered to 85%, the survey would adequately validate both HDSS databases in all considered aspects. The adapted DHS-type sample household survey therefore has potential for validation of HDSS data.